Gènes et Langues : une longue histoire commune ? - Mahé Ben Hamed; Pierre Darlu (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
This text is intended to review how the history of languages and the history of human populations were drawn in parallel and in correspondence, since the 19th century. From the methodological point of view, convergences are numerous, both linguists and population geneticists making use of the same distance methods and the same cladistic or probabilistic approaches. The validity and limits of this analogy between linguistic and genetic evolution of mankind are discussed from recent published examples. Critics are based alternately on how these methods are applied to the linguistic data by phylogeneticists, under the suspicious and critical look of some linguists, and on how the human population geneticists include linguistic classification, often much debated by linguists, within their own genetic concerns.